Enhancing Service Quality At Mai (Madrasah Aliyah Industry) Al-Jabar Batam Through Service Management Training - Lapotulo, Nensi; I Wayan Thariqy Kawakibi Pristiwasa; Sukmamedian, Haufi; Thandzir, Moh; Dailami, Dailami; Yusuf, Abd Rahman (JURNAL KEKER WISATA, 2025)
This community service activity aims to improve the understanding, skills, and attitudes of teachers, administrative staff, and students regarding excellent service implementation. This training employed the participatory action research (PAR) method, which actively involves all stakeholders in planning, executing, and evaluating the activity. The results indicate significant improvements in participants' understanding of the essential concepts of excellent service, including reliability (accuracy), responsiveness (quick response), empathy (emotional learning), assurance (trustworthiness), and tangibles (physical evidence). Participants experienced a shift in perspective, recognizing that excellent service is not merely administrative routines but a professional responsibility for building trust and satisfaction among service recipients. The training also highlighted a paradigm shift from traditional approaches to more participatory and solution-oriented practices, fostering a collaborative culture of continuous service improvement. Through simulations, case studies, and group discussions, participants were equipped with practical skills to apply excellent service concepts effectively. The impact of this training is reflected in improved service quality at MA Industri Al-Jabar, which contributes to enhancing the institution's credibility and satisfaction among students, parents, and the broader community. The findings emphasize the need for sustainable and ongoing training to ensure that excellent service becomes a core cultural practice within educational institutions.